The Role of Teacher Ethics in Developing Students’ Character Values - Faujiah Siregar, Vera; Rezki Marpaung, Sri (International Journal of Students Education, 2023)
A teacher is someone who has an important role in student development, starting from developing students’ talents, providing advice, being a good role model, especially in building good ethics. In this case, school is a place to build student ethics, starting from ethics in speaking to teachers, parents, peers and others, ethics in dressing, ethics in relationships, traffic ethics, business ethics and other ethics. In the world of education, the duties or roles of a teacher towards their students cannot be separated. Where the figure of a teacher is really needed to create the character or personality of the students. This makes teachers work hard and take their time to achieve these tasks. Therefore, the teacher is the main figure in education who has an important role in educating and guiding students to become intelligent human beings who have commendable morals and character. Therefore, the quality of education in a school is largely determined by the ability of a teacher to carry out his duties. Teachers are parents of students in the school environment. For this reason, the role of teachers is very significant in shaping students’ personalities apart from the school environment. This research aims to develop the characteristics of students since they were in elementary school and what the role of a teacher is in developing students’ values. This research uses a literature review method where fifteen articles and five books are analyzed which are the most significant to the research topic. In accordance with the research that has been carried out, the results show that the role of being a teacher in the process of building student ethics is very necessary because as an educator the teacher plays a very important role in the learning process. This research aims to explain the role of teachers in building student ethics.